States United A Survival Guide for Our Democracy - Lydgate, Joanna (Cornell University Press, 2022)
The Laurence and Lynne Brown Democracy Medal, presented by the McCourtney Institute for Democracy at Penn State, recognizes outstanding individuals, groups, and organizations that produce innovations to further democracy in the United States or around the world.Elections are the bedrock of any democracy, but they are under attack in the United States. State legislatures are moving to limit voting rights and seize control of election administration, candidates are refusing to accept election results, and antidemocracy forces are sowing lies and encouraging political violence.The States United Democracy Center is fighting back by equipping state and local officials, law enforcement leaders, and prodemocracy partners with the tools and resources they need to protect free, fair, and secure elections. For this important work, its cofounders are the recipients of the 2022 Brown Democracy Medal. States United was founded during the 2020 election and continues to be led by Joanna Lydgate, former chief deputy attorney general of Massachusetts; Norman Eisen, former ambassador to the Czech Republic and special assistant to President Barack Obama for ethics and government reform; and Christine Todd Whitman, former New Jersey governor and Environmental Protection Agency administrator.